SeqSNP-based genic markers reveal genetic architecture and candidate genes for low nitrogen tolerance in tropical maize inbred lines - Abu, P.; Badu-Apraku, B.; Ifie, B.E.; Eleblu, J.S.Y.; Ehemba, L.; Tongoona, P.; Offei, S. (Frontiers Media, 2025)
Maize production in sub-Saharan Africa (SSA) faces significant challenges due to low soil nitrogen. To enhance breeding efficiency for low nitrogen tolerance, identifying quantitative trait loci (QTLs) in tropical germplasm is crucial to facilitate marker-assisted selection (MAS). In this study, gene targeting markers (GTM) derived from sequence-based single nucleotide polymorphisms (SeqSNP) were utilized to analyse the population structure and identify potential candidate genes associated with tolerance to low nitrogen. A total of 150 extra-early quality protein maize (QPM) inbred lines were assessed under both low (LN) and high (HN) nitrogen, followed by genotyping with 2,500 SeqSNPs targeting genes previously reported for LN tolerance-related traits. Population structure analysis revealed six sub-populations. Association mapping analysis revealed 15 significant single nucleotide polymorphisms (SNPs) linked to several key traits. Specifically, two SNPs each were associated with the low nitrogen base index (LNBI), which combines grain yield with other agronomic traits under low nitrogen, and the low nitrogen tolerance index (LNTI), a measure of grain yield performance in high nitrogen environments relative to low nitrogen environments.